Back Cover: Magnetic‐Field‐Stimulated Efficient Photocatalytic N2 Fixation over Defective BaTiO3 Perovskites (Angew. Chem. Int. Ed. 21/2021). Issue 21 (6th April 2021) - Zhao, Zhao; Wang, Dandan; Gao, Rui; Wen, Guobin; Feng, Ming; Song, Guangxin; Zhu, Jianbing; Luo, Dan; Tan, Huaqiao; Ge, Xin; Zhang, Wei; Zhang, Yujun; et al.
Abstract : Magnetic field stimulated photocatalytic N2 fixation over defective BaTiO3 perovskites is described by Ming Feng, Haibo Li, Zhongwei Chen, and co‐workers in their Research Article on page 11910 . The electromagnetic synergistic effect promotes N2 adsorption and activation while facilitating fast charge separation under UV/Vis irradiation. This study offers an alternative route for exploring photocatalytic N2 fixation materials.